Introducing Traditional Herb-based Medicine ‘Boreh’ on Wellness Tourism in Bali - Eka Ari Suhendra (Bali Tourism Board, 2022)
Since ancient times, people have recorded their knowledge of processing various herbs into medicine. In Bali, it can be found scattered on the island under the term Lontar Usadha, written on dried-Borassus leaves. From many types of traditional medicine and treatments in Lontar Usadha, Boreh has endured through centuries. There are three types of Boreh known by Balinese folks. It is classified according to their effect on the body: Boreh anget, Boreh miyik, and Boreh tis. Despite its popularity as a health treatment that has endured throughout time, it should be admitted that society's understanding regarding the ingredient's composition, processing steps, and the applying method is strongly influenced by the available information sources around them, as well as the ingredients. To appreciate and conserve the knowledge of Boreh making, the Bali Provincial Culture Office held a Boreh-making competition. On the spot, the public could see various Boreh ingredients that most Balinese rarely find today. On the other hand, the Government has a strategic plan to develop Wellness tourism as a new activity option when tourists visit Bali. In line with the effort to introduce Boreh as a traditional medicine from Bali, tourists can experience traditional treatment from their hotel or spa.